Catalogación de los recursos educativos abiertos (rea), desarrollados por la carrera de pedagogía de las ciencias experimentales informática en el periodo octubre 2019 - septiembre 2020. - Medina Medina, Damián Ricardo (2021)
The main purpose of the present investigation was to catalog the Open Educational Resources developed by the students of the fifth cycle of the Computer Science Experimental Pedagogy Career in the period October 2019 - September 2020. This investigation is of a descriptive transectional type and for its execution it is used a non-experimental analytical methodology, the instruments that were used for the collection of Open Educational Resources were: an unstructured interview with the teacher of the Programming I subject, during the period October 2019 - March 2020, and a survey directed to the students. students who developed digital educational resources in the Programming I subject during the period April 2020 - September 2020, thus a cataloging and evaluation sheet of educational resources was also used, which evaluated the dimensions: pedagogical, technical, management, design, social, ethical and legal, development and resp professional responsibility, where the following results were obtained: thirty-four Open Educational Resources were collected, of which only five of them could be classified, in addition a database was implemented through an Open Digital Repository, for the Pedagogy Career of the Therefore, it could be concluded that 4 of 34 Open Educational Resources obtained a score from 1 to 41, which are called "Not Relevant", 25 reached a score of 42 to 83, being considered as "Modifiable" , and 5 reached a score of 84 to 124, obtaining a denomination of "Relevant", which were classified and included in the database.